Peran Kepemimpinan Transformasional dan Literasi Digital terhadap Kompetensi Pedagogis Guru dalam Pengintegrasian Teknologi - Haryanti, Marta Lenah; Purbojo, Rijanto (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The success of improving the quality of educational institutions depends on the involvement of a transformational leadership style and digital literacy skills, which are part of teachers' professional competence in using Information and Communication Technology (ICT). This research aims to measure the influence of perceptions of transformational leadership and digital literacy on teachers' pedagogical competence in integrating technology through the Technological Pedagogical Content Knowledge (TPACK) framework. The method used in this research is quantitative research with a simple and multiple linear regression analysis approach. The respondents were 78 teachers at teaching levels 7-12 in two national schools who completed a digital questionnaire. The results show that transformational leadership influences teacher pedagogical competence, digital literacy influences teacher pedagogical competence, and perceptions of transformational leadership and digital literacy influence teacher pedagogical competence in integrating technology. Based on the TPACK framework, which is used as a link between abilities and skills from pedagogical, content, and technology perspectives, the technology component needs to be improved to increase teacher confidence in integrating technology into learning.